Pengembangan Worksheet Digital Berbasis Kearifan Lokal Dan Karakter Pada Kelas Iv Tema Delapan Daerah Tempat Tinggalku - Hanifah, Hanifah; Eko Putro W, Sugeng; Suyoto, Suyoto (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2022)
This study aims to determine the feasibility and practicality of digital worksheets based on local wisdom and character in grade 4 theme 8 My Living Area. This type of research is development research with AADIE (Analysis), (Design), (Development), (Implementation), and (Evaluation) models. Data collection techniques include interviews, observation, document analysis, and questionnaires. The results of the feasibility based on three experts namely material experts, media experts, and practitioners obtained an average of 3.7 with very feasible criteria. The practicality rest was lots obtained from the student response questionnaire in the limited trial with a percentage of 70％ with a very practical classification and 30％ with a practical classification. In extensive trials, the results were obtained with a percentage of 55％ with a very practical classification and 45% with a practical classification. In addition to the practical results obtained from student responses, there are also results of learning implementation. At the first meeting, the average was 3.35 with a very practical classification, the second meeting obtained an average of 3.67 with a very good classification, and the third meeting obtained an average of 3.80 with a very good classification. Based on the results obtained from the feasibility and practicality above, it can be concluded that the digital worksheet based on local wisdom and character in grade 4 theme 8 My Living Area is feasible and practical so that it can be used in learning. Based on the results of the worksheets based on local wisdom and character in class 4 Theme 8 My Living Area, there was an increase in student learning outcomes both from local wisdom and the application of character, as well as an increase in students' interest in knowing local wisdom in Purworejo Regency.